2020
DOI: 10.21203/rs.3.rs-40780/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Decoding semi-automated title-abstract screening: a retrospective exploration of the review, study, and publication characteristics associated with accurate relevance predictions

Abstract: Abstract Background We evaluated the benefits and risks of using the Abstrackr machine learning (ML) tool to semi-automate title-abstract screening, and explored whether Abstrackr’s predictions varied by review or study-level characteristics. Methods For 16 reviews we screened a 200-record training set in Abstrackr and downloaded the predicted relevance of the remaining records. We retrospectively simulated the liberal-accelerated screening approach: one reviewer scr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
(49 reference statements)
0
1
0
Order By: Relevance
“…Interestingly, the specific criteria with worse prediction value differed in these algorithms compared to machine learning approaches. A recent study on machine learning revealed a propensity for incorrect prediction in identifying observational studies, reviews, studies with low risk of bias and older citations [ 22 ]. Additionally, we found a significant decrease in loss of sensitivity when two or more exclusion criteria were selected.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the specific criteria with worse prediction value differed in these algorithms compared to machine learning approaches. A recent study on machine learning revealed a propensity for incorrect prediction in identifying observational studies, reviews, studies with low risk of bias and older citations [ 22 ]. Additionally, we found a significant decrease in loss of sensitivity when two or more exclusion criteria were selected.…”
Section: Discussionmentioning
confidence: 99%